Diet in Peru's pre-Hispanic central coast - Gerdau-Radonic, K.; Goude, G.; Castro de la Mata, P.; André, G.; Schutkowski, H.; Makowski, K. (Elsevier, 2015)
The Tablada de Lurín cemetery (200 BC–AD 200; Lima, Peru) is characterised by two mortuary phases. Based on associated grave finds and the lack of habitation sites near the cemetery, it has been hypothesised that both burial populations came from a certain distance of the site (ca. 20 km) and that they relied on land rather than marine resources. We tested these hypotheses, based on material culture, through stable isotope analysis. The aim was to understand the populations' diet and geographic origins. We sampled 47 human individuals and eleven sets of faunal remains from both phases for stable isotope analysis (carbon, nitrogen, sulphur and oxygen) of bone and dental collagen, and apatite. Modern samples of autochthonous food were also tested as a baseline for comparison. The results showed preservation differences between the remains from both phases. Individuals from Phase 1 provided the best isotopic dataset and showed consumption of protein from marine resources and C4 plants. On the other hand, bioapatite carbon and oxygen stable isotope results from both phases highlighted differences in C4 plant consumption and individuals of possible non-local origin. The results underline the need to study further the effect of brewed or cooked beverages on bioapatite oxygen levels. Finally, results from Phase 1 fit with the broader dietary pattern evident in other Andean sites, where coastal populations consumed marine protein and C4 plants, as opposed to highland populations who relied on terrestrial protein sources and C3 plants.
Keywords: Maize; Seafood; Environment; Stable isotopes; Andes; Pre-Columbian; https://purl.org/pe-repo/ocde/ford#5.04.03